Hypoxia-pretreated mesenchymal stem cell-derived exosomes-loaded low-temperature extrusion 3D-printed implants for neural regeneration after traumatic brain injury in canines - Liu, Xiaoyin; Wang, Jingjing; Wang, Peng; Zhong, Lin; Wang, Shan; Feng, Qingbo; Wei, Xin; Zhou, Liangxue (Frontiers in Bioengineering and Biotechnology, 2022)
Regenerating brain defects after traumatic brain injury (TBI) still remains a significant difficulty, which has motivated interest in 3D printing to design superior replacements for brain implantation. Collagen has been applied to deliver cells or certain neurotrophic factors for neuroregeneration. However, its fast degradation rate and poor mechanical strength prevent it from being an excellent implant material after TBI. In the present study, we prepared 3D-printed collagen/silk fibroin/hypoxia-pretreated human umbilical cord mesenchymal stem cells (HUCMSCs)-derived exosomes scaffolds (3D-CS-HMExos), which possessed favorable physical properties suitable biocompatibility and biodegradability and were attractive candidates for TBI treatment. Furthermore, inspired by exosomal alterations resulting from cells in different external microenvironments, exosomes were engineered through hypoxia stimulation of mesenchymal stem cells and were proposed as an alternative therapy for promoting neuroregeneration after TBI. We designed hypoxia-preconditioned (Hypo) exosomes derived from HUCMSCs (Hypo-MExos) and proposed them as a selective therapy to promote neuroregeneration after TBI. For the current study, 3D-CS-HMExos were prepared for implantation into the injured brains of beagle dogs. The addition of hypoxia-induced exosomes further exhibited better biocompatibility and neuroregeneration ability. Our results revealed that 3D-CS-HMExos could significantly promote neuroregeneration and angiogenesis due to the doping of hypoxia-induced exosomes. In addition, the 3D-CS-HMExos further inhibited nerve cell apoptosis and proinflammatory factor (TNF-α and IL-6) expression and promoted the expression of an anti-inflammatory factor (IL-10), ultimately enhancing the motor functional recovery of TBI. We proposed that the 3D-CS-loaded encapsulated hypoxia-induced exosomes allowed an adaptable environment for neuroregeneration, inhibition of inflammatory factors and promotion of motor function recovery in TBI beagle dogs. These beneficial effects implied that 3D-CS-HMExos implants could serve as a favorable strategy for defect cavity repair after TBI.